A Translation Analysis Of Verbs And Verb Phrases In 9 Summers 10 Autumns From The City Of Apples To The Big Apple Into Dari Kota Apel Ke The Big Apple By Iwan Setiawan - Kurniasari, Dini, Dr. Dwi Haryanti, M.Hum, Mauly Halwat Hikmat, Ph. D (2015)
This research belongs to decsriptive qualitative research. The research purposes are to classify the translation shift of verbs and verb phrases in "9 Summers 10 Autumns From the City of Apples to the Big Apple" and its translation "Dari Kota Apel ke The Big Apple" and to describe the quality of the translation of the novel. The data of this research are verbs and verb phrases and their translation. The data sources are novel "9 Summers 10 Autumns From the City of Apples to the Big Apple" and its translation "Dari Kota Apel ke The Big Apple". The writer uses documentation and questioner as the method of collecting data in this research. The results of the research show that first, there are 5 shifts of English verb. They are: 1) structure shift 1 data or 0,11%, 2)class shift 17 data or 2,01%, 3) intra-system shift 105 data or 12,41%, 4) unit shift 3 data or 0,35%, 5) level shift 46 data or 5,44%, and 324 data or 38,30% that is not analyzed There are 2 shifts of English verb phrase. They are: 1) Structure shift 8 data or 0,94%, and 2) level shift 126 data or 14,89%, and 217 data or 25,65% that is not analyzed. Second, there are 3 shifts of quality translation. They are 1)Accuracy that are divided into 3, Accurate 115 data or 24,00% , less accurate 316 data or 65,97%, and inaccurate 48 data or 10,02%, 2) Acceptability that are divided into 2, acceptable 377 data or 78,70%, and less acceptable 102 data or 21,29%, 3) Readability that is divided into 2, high readability 416 data or 96,24%, and medium readability 18 data or 3,76%.